Evaluation of detectors for acquisition of pristine depth‐dose curves in pencil beam scanning. (8th November 2015) - Bäumer, Christian; Koska, Benjamin; Lambert, Jamil; Timmermann, Beate; Mertens, Thierry; Talla, Patrick Takoukam
Abstract : Acquisition of quasi‐monoenergetic ("pristine") depth‐dose curves is an essential task in the frame of commissioning and quality assurance of a proton therapy treatment head. For pencil beam scanning delivery modes this is often accomplished by measuring the integral ionization in a plane perpendicular to the axis of an unscanned beam. We focus on the evaluation of three integral detectors: two of them are plane‐parallel ionization chambers with an effective radius of 4.1 cm and 6.0 cm, respectively, mounted in a scanning water phantom. The third integral detector is a 6.0 cm radius multilayer ionization chamber. The experimental results are compared with the corresponding measurements under broad field conditions, which are performed with a small radius plane‐parallel chamber and a small radius multilayer ionization chamber. We study how a measured depth‐dose curve of a pristine proton field depends on the detection device, by evaluating the shape of the depth‐dose curve, the relative charge collection efficiency, and intercomparing measured ranges. Our results show that increasing the radius of an integral chamber from 4.1 cm to 6.0 cm increases the collection efficiency by 0%–3.5% depending on beam energy and depth. Ranges can be determined by the large electrode multilayer ionization chamber with a typical uncertainty of 0.4 mm on a routine basis. The large electrode multilayer ionization chamber exhibits a small distortion in the Bragg Peak region. This prohibits its use for acquisition of base data, but is tolerable for quality assurance. The good range accuracy and the peak distortion are characteristics of the multilayer ionization chamber design, as shown by the direct comparison with the small electrode counterpart. PACS number: 87.55.Qr